Intake and digestibility of lambs fed with cashew bagasse in sorghum substitution in the ensiling (Research, Society and Development, 2020)
This study was conducted to evaluate the effects substitution of forage of sorghum by cashew bagasse dehydrated at the time of ensiling on the performance of feedlot lambs. Were used 32 male sheep, not castrated and crossbreed of breeds Morada Nova (½) and Santa Inês (½), with an average initial body weight of 15.1 ± 0.71 kg, confined and with 14 days of adaptation. The experimental diet consisted of silage prepared with 0; 8; 16; 24% of dehydrated cashew bagasse (DCB) replacing the forage of sorghum (Sorghum bicolor) at the time of ensiling, offered in two daily meals, being allowed a daily surplus of at most 10%, without providing concentrate supplementation. Were evaluated the dry matter intake (DMI) and nutrients, and their digestibility until 120 days in confinement. The data were submitted to analysis of variance and the effect of the replacement levels assessed by regression analysis at 5% significance. The increase in BCD levels promoted quadratic response to the intake of dry matter, crude protein, total digestible nutrients, non-fiber carbohydrates (CCNF) and body slaughter weights. The digestibility of dry matter, organic matter, insoluble fiber in acid detergent, total carbohydrates and non-fibrous carbohydrates presented behavior linear increasing as it replaced the forage of sorghum by BCD. This indicates, therefore, the replacement of 24% of by fodder sorghum bagasse cashew dehydrated at the time of ensiling.